Em busca da influência global: a estratégia de soft power do Catar por meio da Copa do Mundo FIFA de 2022 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2024)
The role of soft power in football is discussed by examining how a country’s influence and attractiveness can be exerted through sports. The concept of “sportswashing” is introduced, where large-scale sporting events are hosted to improve a country’s image—often as a way to obscure controversial issues. The importance of sovereign wealth funds is crucial for Qatar as a key player in the global gas trade. Additionally, Qatar is strategically located, rich in hydrocarbon reserves, and occupies a vital position in the Persian Gulf. As an exploratory research, this paper seeks to understand how Qatar uses sports as a soft power mechanism, exploring its relationship with the 2022 FIFA World Cup, symbolic power, and the global consequences of these dynamics. The research involved an extensive review of academic literature, followed by critical analysis and synthesis of information from reports and scholarly articles to support the study’s development. Through sports, Qatar has forged strategic ties that have expanded its diplomatic presence and strengthened bilateral relations. This is a relevant topic to address, as it reveals “sportswashing” strategies and their implications for contemporary energy geopolitics.
Keywords: Geopolítica; Diplomacia Esportiva - Copa do Mundo da FIFA 2022; Geopolítica; Política Internacional; CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL; ODS 16 – Paz, justiça e instituições eficazes; ODS 17 – Parcerias e meios de implementação; ODS 8 – Trabalho decente e crescimento econômico